Analisis Pengaruh Serangan Black Hole Terhadap Protokol AODV Pada Mobile Ad Hoc Network dengan Lingkungan Pergerakan Dinamis - Daffarez Elguska; Reza Andria Siregar; Rakhmashany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
MANET is one of the wireless technologies that consists of several mobile nodes that are composed without a fixed infrastructure. This technology has issues in the security aspect because it is built without a fixed infrastructure. One of the attacks on the MANET network that is often encountered is a black hole attack. A black hole attack is an attack that can drag all data streams in a network by sending fake reply messages to the data sending node stating that the black hole node is the fastest route node to the destination node then data is retrieved by the black hole and the data being dropped. In this study the authors use AODV routing protocol, Random Based Mobility (Random Waypoint, Random Walk, Random Direction) and simulation parameters of different nodes (10, 25, 50) with black hole nodes placed in 5 different positions. This study will analyze the impact caused by the attack of a black hole with the testing parameters of packet delivery ratio. The study was conducted using the NS3 simulator and animated on NetAnim. The test results showed the black hole attack is significant work on all mobility models and all number of nodes with mostly packet delivery ratio value is 0% in all positions of the black hole node.